EKSPLORASI BUSANA PESTA COCKTAIL UNTUK REMAJA DENGAN SUMBER IDE TERUMBU KARANG PECTINIA LACTUCA - Wahyu Eka Priana Sukmawaty (Universitas Ciputra Surabaya, 2021)
This study aims to: (1) describe cocktail party dress suitable for young women aged 17-21 years with the source of the idea of coral reef Pectinia Lactuca; and (2) describe the adolescent response to the product of exploration of cocktail party fashion with the source of the idea of coral reef Pectinia Lactuca. This research was conducted using descriptive methods. Respondents were taken as many as 30 teenagers in Piyungan Bantul District Yogyakarta aged 17-21 years. Data collection techniques using questionnaires and documentation. Data analysis techniques using descriptive data analysis. The results of this fashion product exploration research are 1) Based on the results of the study results of the exploration of cocktail party fashion for teenagers with the source of the idea of coral reefs Pectinia Lactuca produced two unique and beautiful fashion pieces. For party fashion, the first model consisted of a blouse and a balloon skirt. The balloon skirt was made with the smock technique to give the impression of Pectinia Lactuca coral reef and used brown taffeta fabric and a soft blue draperies blouse to give the impression of the ocean. As for the second model party dress in the form of a mini dress with a silhouette of H with obi. On the sleeves and bottom of the dress is given a smock section, while the body part with tie-dye technique is blue.2) ) The response of teenagers to the first model cocktail party fashion with the category Of conformity of the use of materials with the design for the first cocktail fashion model can be concluded that 83% of respondents who stated very appropriate, 10% of respondents who stated appropriate, and 7% of respondents who stated inappropriate and for the second cocktail fashion model can be concluded that 87% of respondents who stated very appropriate and 13% of respondents who stated appropriately. As for the category of colour conformity with the source of ideas for the first cocktail, fashion model can be concluded that 90% of respondents stated very appropriate, 7% of respondents stated appropriate, and 3% of respondents stated inappropriate and for the second cocktail, fashion model can be concluded that 93% of respondents who stated very appropriate and 7% of respondents who stated appropriately.